HLTH - Nevid, Jeffrey S.; Rathus, Spencer A. (Wadsworth, 2013)
Created through a "student-tested, faculty-approved" review process with over 100 students and faculty, HLTH is an engaging and accessible solution to accommodate the diverse lifestyles of today's learners